2022
DOI: 10.3389/fpain.2022.933422
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidence for Intrathecal Management of Neuropathic Pain Following Spinal Cord Injury

Abstract: A high prevalence of patients with spinal cord injury (SCI) suffer from chronic neuropathic pain. Unfortunately, the precise pathophysiological mechanisms underlying this phenomenon have yet to be clearly elucidated and targeted treatments are largely lacking. As an unfortunate consequence, neuropathic pain in the population with SCI is refractory to standard of care treatments and represents a significant contributor to morbidity and suffering. In recent years, advances from SCI-specific animal studies and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Oral Res has the characteristics of rapid absorption but low bioavailability ( Walle et al, 2004 ). Intrathecal drug delivery has been considered as a highly favorable pharmacologic delivery system given that spinal cord dorsal contains a majority of therapeutic drug target ( Karri et al, 2022 ). Previous research reported that intrathecal administration with Res had higher bioavailability and blood brain penetrability to treat rat intracranial glioblastomas compared to systematic administration ( Shu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oral Res has the characteristics of rapid absorption but low bioavailability ( Walle et al, 2004 ). Intrathecal drug delivery has been considered as a highly favorable pharmacologic delivery system given that spinal cord dorsal contains a majority of therapeutic drug target ( Karri et al, 2022 ). Previous research reported that intrathecal administration with Res had higher bioavailability and blood brain penetrability to treat rat intracranial glioblastomas compared to systematic administration ( Shu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammatory activation of glial cells and immune cells after nerve injury is being increasingly implicated in neuropathic pain (Chambel et al, 2020;Karri et al, 2022). EVs pose tremendous antiinflammatory capacity following nerve injury and the roles of EVs in neuropathic pain will be a particularly interesting area of future inquiry.…”
Section: Extracellular Vesicles Regulate Neuropathic Pain Via Neuroin...mentioning
confidence: 99%